MENINGKATKAN HASIL BELAJAR PJOK DENGAN MENGGUNAKAN MEDIA GRAFIS DI SDN 028 KUBANG JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Nurbaiti Nurbaiti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the learning result of physical education of sports and health which is still low. This studyaims to improve student learning outcomes class III.A Elementary School 028 Kubang Jaya District Siak HuluKampar District. This research uses classroom action research with two cycles with graphic media approach.Based on the result of the research before the action average student score 46,80 (enough), the individual masteryof only 4 students and 18.18% classical completeness; on the first cycle average learning outcomes 63.16 (enough),individual completeness obtained 14 students and 63.60%% classical completeness; and in cycle II the averagevalue of 80.45 (good) and classical completeness is as much as 22 students or 100%. Thus the use of graphic mediais successful or can improve learning outcomes physical education sports and health Class III.A Elementary School028 Kubang Jaya District Siak Hulu Kampar District.